Regulation of Lymphocyte Function by PPARγ: Relevance to Thyroid Eye Disease-Related Inflammation. (24th December 2007) - Lehmann, G. M.; Garcia-Bates, T. M.; Smith, T. J.; Feldon, S. E.; Phipps, R. P.
Abstract : Thyroid eye disease (TED) is an autoimmune condition in which intense inflammation leads to orbital tissue remodeling, including the accumulation of extracellular macromolecules and fat. Disease progression depends upon interactions between lymphocytes and orbital fibroblasts. These cells engage in a cycle of reciprocal activation which produces the tissue characteristics of TED. Peroxisome proliferator-activated receptor-γ (PPARγ ) may play divergent roles in this process, both attenuating and promoting disease progression. PPARγ has anti-inflammatory activity, suggesting that it could interrupt intercellular communication. However, PPARγ activation is also critical to adipogenesis, making it a potential culprit in the pathological fat accumulation associated with TED. This review explores the role of PPARγ in TED, as it pertains to crosstalk between lymphocytes and fibroblasts and the development of therapeutics targeting cell-cell interactions mediated through this signaling pathway.